2012
DOI: 10.1089/aid.2011.0219
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Proviral Load and Vertical Transmission of Human T Cell Lymphotropic Virus Type 1 in Guinea-Bissau

Abstract: The relative importance of routes of transmission of human T cell lymphotropic virus type 1 (HTLV-1) in Guinea-Bissau is largely unknown; vertical transmission is thought to be important, but there are very few existing data. We aimed to examine factors associated with transmission in mothers and children in Guinea-Bissau, where HTLV-1 is endemic (prevalence of 5% in the adult population). A cross-sectional survey was performed among mothers and their children (aged <15 years) in a rural community in Guinea-Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…In fact, several studies reported that indicators of lower socioeconomic status, such as lower educational level and low income, are associated with HTLV-1 transmission 2 and to MTCT 2 , 34 , 35 . Transmission occurred regardless of the sex of the child, but this data is controversial, since some studies have associated a higher risk of transmission to males 23 or females 22 exposed children, whereas others found a similar transmission risk for boys and girls 24 , 27 , 28 , 30 , 36 , 37 . However, the small sample size is a limitation to influence the child infection from other factors, such as history of blood transfusion, cesarean delivery or maternal coinfection with HIV, HTLV-2, HBV or an association of HIV/HCV.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies reported that indicators of lower socioeconomic status, such as lower educational level and low income, are associated with HTLV-1 transmission 2 and to MTCT 2 , 34 , 35 . Transmission occurred regardless of the sex of the child, but this data is controversial, since some studies have associated a higher risk of transmission to males 23 or females 22 exposed children, whereas others found a similar transmission risk for boys and girls 24 , 27 , 28 , 30 , 36 , 37 . However, the small sample size is a limitation to influence the child infection from other factors, such as history of blood transfusion, cesarean delivery or maternal coinfection with HIV, HTLV-2, HBV or an association of HIV/HCV.…”
Section: Discussionmentioning
confidence: 99%
“…This cohort was established in 1991, and subjects were examined in 1996, 2003, and 2006. In addition, in 2004 a cross-sectional study was performed to examine mother-to-child transmission of HTLV-1 [19]. HTLV-1 prevalence has been stable at around 5% in Caio throughout this period [15].…”
Section: Methodsmentioning
confidence: 99%
“…All complete LTR sequences obtained from mother-child pairs from the vertical transmission study in 2004 were also used in the current analysis (accession numbers JN655856 to JN655872). [19]. Samples for p24 sequencing were randomly selected in 2009 from stored DNA samples for an as yet unpublished immunological study.…”
Section: Methodsmentioning
confidence: 99%
“…8 While the genetic variability of the HTLV-I proviral sequence is relatively low when compared to other viruses such as human immunodeficiency virus (HIV) and hepatitis C virus (HCV), epidemiologically linked infections have been identified. [10][11][12] In HTLV-I-endemic areas such as southwestern Japan, the Caribbean, sub-Saharan Africa, South America, and parts of Iran, seroprevalence rates range from less than 5% to 10%. 13 Infection is lifelong with transmission of the virus primarily through breast milk, sexual contact, blood transfusion, or from sharing needles in intravenous drug use.…”
mentioning
confidence: 99%